Controlled release of FGF-2 and BMP-2 in tissue engineered periosteum promotes bone repair in rats. (9th January 2018) - Yin, Jie; Qiu, Sujun; Shi, Benchao; Xu, Xiaolong; Zhao, Yunfei; Gao, Junhuai; Zhao, Shengli; Min, Shaoxiong
Abstract: The aim of this study was to prepare chitosan–collagen (CS/COL) scaffolds that could release fibroblast growth factor-2 (FGF-2) and bone morphogenetic protein 2 (BMP-2), and to study the effect of this scaffold on bone repair. By improving the double emulsion/solvent evaporation technique, BMP-2 was encapsulated in poly(lactic acid)–poly(ethylene glycol)–poly(lactic acid) (PELA) microcapsules, to the surface of which FGF-2 was attached. The CS/COL scaffold carrying the microcapsules was prepared by freeze-drying. Periosteum derived cells (PDCs) were extracted and cultured on the scaffolds to study their proliferation and differentiation on the scaffolds. In addition, the effects of the scaffolds were investigated on rats with skull defects by micro-computed tomography and histology. We successfully prepared PELA microcapsules with external adherence to FGF-2 and encapsulated with BMP-2. The CS/COL scaffolds were porous and PDCs adhered, proliferated and underwent osteogenic differentiation on the scaffolds. The sequential release of FGF-2/BMP-2 had better osteogenic efficacy than other groups. Our results suggest that CS/COL scaffolds that bind FGF-2 and BMP-2 in combination with PDCs could be a promising new strategy for tissue engineering periosteum.